Design of Submerged Wave-Induced Forcing Elements to Power a Linear Generator - Md Fadhli Helmi B Noor Kamaruzaman, Md Fadhli Helmi (2008)
The objective of this project is to generate renewable energy using the ocean energy. This project differs than conventional Wave Generator where the wing was submerged underneath the sea where it uses the sea current flow that more stable than the normal wave height. The project translates and captures the energy from the Wave- Induced Element and converts it into electricity.